Stakeholders’ Engagement in the Sustainability Reporting of Companies: A study within the context of Cameroon - TEGOFACK, Bleck Capouell; KAMGANG FODJO, Ghislain Justice (Revue du contrôle, de la comptabilité et de l’audit, 2021)
The preparation of a sustainability report requires stakeholder engagement as a mandatory stage for the publication of a complete, credible and useful document to the stakeholders. Hence, the purpose of this paper is to empirically find out whether this requirement is considered by companies in their sustainability reporting practice by examining the level of stakeholders’ engagement in sustainability reporting of companies in Cameroon. To achieve this, a multiple case study was conducted where the stakeholder engagement disclosure items (characteristics) were evaluated through a content analysis of seven sustainability reports of three companies for the periods 2015 to 2017. The investigation reveals that the level of stakeholder engagement in the sustainability reporting of companies is averaged. The stakeholder engagement disclosure item that was regularly disclosed is the “identification of stakeholders” whereas, the “perception” (testimony) of stakeholders on previous reports was the least disclosed items.